Development of Microsoft-Based E-learning Media for Elementary School Students - Fige Arief Kusumo; Bambang Subali; Sunarto Sunarto (International Conference on Science, Education, and Technology, 2022)
This study aims to develop Microsoft-based e-learning media used for distance learning. This research was conducted to add learning media in elementary schools. Media by combining Microsoft-based learning and evaluation. The study was learn by google meet application. The research has steps: (1) Reviewing e-learning research journals; (2) Designing learning designs; (3) Designing Microsoft-based learning media; (4) Expert validation of lecturers and teachers; (5) take data on student responses to learning media. Based on the analysis results of the Expert, it was obtained that the average V Aiken calculation was 0.72, which had the criteria of Sufficiently Valid. The percentage agreement is 97% which has very good criteria. Based on the results of the teacher's assessment analysis, the average V aiken calculation is 1.28 which has very valid criteria. The percentage agreement is 97% which has very good criteria. The recapitulation shows that this Microsoft-based e-learning media product can be implemented at Fifth Grader of Elementary School learning.